Medical Oxygen Concentrators for Releasing Seed Dormancy. Issue 5 (1st September 2015) - Brenner, David M.; Dekker, Jack; Niemi, Jarad; Pfiffner, Lisa
ABSTRACT: A new method is demonstrated for using concentrated oxygen (O2 gas) to release seed dormancy. Concentrated O2 gas in air is known to release seed dormancy in some seeds, including some foxtail ( Setaria ) species. New medical equipment makes O2 gas easier to work with than before, so laboratories working with dormant seeds can now use concentrated O2 gas as a seed treatment on a production basis. Use of medical O2 gas concentrators is simpler and safer than using O2 gas supplied by pressurized gas cylinders. Suitable medical O2 gas concentrators in new or used condition are readily available, operate on standard electrical current, and deliver O2 gas with low‐pressure tubes and fittings. Resealable plastic bags are inflated with concentrated O2 gas and then sealed as seed treatment chambers. This use of concentrated O2 gas is confirmed to significantly increase the germination of dormant seeds of giant foxtail ( Setaria faberi Herrm) and plains bristlegrass ( S. macrostachya Kunth).